2007
DOI: 10.1016/j.ijsolstr.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The uniaxial tension of particulate composite materials with nonlinear interface debonding

Abstract: Debonding of particle/matrix interfaces can significantly affect the macroscopic behavior of composite material. We have used a nonlinear cohesive law for particle/matrix interfaces to study interface debonding and its effect on particulate composite materials subject to uniaxial tension. The dilute solution shows that, at a fixed particle volume fraction, small particles lead to hardening behavior of the composite while large particles yield softening behavior. Interface debonding of large particles is unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Kari et al [319] showed that, for a given volume fraction, the influence of the size of the spherical particles on the effective material properties is not significant in the case of linear elasticity. The effect of interface debonding and particle size on behavior of particulate composite materials was studied by Tan et al [320]. Based on their observations, small and large particles yield hardening and softening behavior, respectively.…”
Section: 22mentioning
confidence: 99%
“…Kari et al [319] showed that, for a given volume fraction, the influence of the size of the spherical particles on the effective material properties is not significant in the case of linear elasticity. The effect of interface debonding and particle size on behavior of particulate composite materials was studied by Tan et al [320]. Based on their observations, small and large particles yield hardening and softening behavior, respectively.…”
Section: 22mentioning
confidence: 99%
“…[29][30][31][32]) and high volume fraction [33]. However, additional structural factors, such as non-random and non-periodic distribution [7] and de-bonding between particles and matrix, are not well modelled by any of these traditional analytical methods [34,35], necessitating the application of multiscale numerical models [36].…”
Section: Multiscale Modellingmentioning
confidence: 99%
“…CGMs form a wide class of materials with a similar microstructure consisting of densely packed particles and a solid matrix filling the interstitial space and sticking to the particles. Some examples are mortars, concrete and asphalt (aggregates of various sizes glued to each other by a cement paste) [1], solid propellants and high explosives (large volume of energetic particles in a polymeric binding matrix) [2], sedimentary rocks (sandstones, conglomerates and breccia) [3], and some biomaterials such as the wheat endosperm (starch granules forming a compact structure bound together by a protein matrix) [4][5][6]. In the major numerical methods used to simulate granular materials (Contact Dynamics (CD), Discrete Element Method (DEM)), the particles are treated as solid objects that interact only at their contact points.…”
Section: Sub-particle Stress Transmission In Granular Solidsmentioning
confidence: 99%